Penerbangan Berkelanjutan: Perlindungan Hak Masyarakat Adat Berbasis Nilai Pancasila - Kurnianto, Benny; Abdusshomad, Alwazir; Kalbuana, Nawang (Indo-MathEdu Intellectuals Journal, 2024)
In Indonesia, the protection of indigenous peoples' rights in the context of the aviation industry based on Pancasila values faces complex challenges. Although there have been efforts to establish a legal basis that respects these rights, their implementation in the aviation sector is still limited. This research aims to explore the implementation of Pancasila values in the protection of indigenous peoples' rights in the aviation sector and identify collaborative steps that can be taken by the government, the aviation industry, and other stakeholders. Using a descriptive qualitative approach through literature studies, this study evaluates challenges such as the lack of participation of indigenous peoples in aviation project decisions and the lack of effective law enforcement. The results show that cooperation between governments, airlines, civil society, and indigenous peoples is essential to strengthen the protection of their rights. It is also necessary to evaluate the impact of airport development policies to ensure the protection of land rights and the sustainability of indigenous peoples' culture. The involvement of indigenous peoples in the planning of aviation projects is a concrete step to ensure the alignment of aviation infrastructure development with Pancasila values and the rights of indigenous peoples